Anti-diabetic effect of baicalein is associated with the modulation of gut microbiota in streptozotocin and high-fat-diet induced diabetic rats. (July 2018) - Zhang, Bowei; Sun, Wenlong; Yu, Na; Sun, Jin; Yu, Xiaoxia; Li, Xia; Xing, Yan; Yan, Dong; Ding, Qianzhi; Xiu, Zhilong; Ma, Baiping; Yu, Liyan; et al.
Graphical abstract: Highlights: Baicalein improved insulin-resistance and systemic inflammation in diabetic rats. Baicalein modulated gut microbiota composition and enhanced gut barrier function. SCFA-producing bacteria were up-regulated and pathogens were down-regulated. Bacteroidales S24-7 and Bacteroides were found to be putative beneficial bacteria. Abstract: Baicalein, a dietary flavonoid, is the major constituent of Oroxylum indicum and Scutellaria baicalensis which are consumed as teas or dietary supplements in Asia, European, and the United States. The compound exhibits a variety of bioactivities despite its limited bioavailability. In the present work, 4-week treatment of baicalein significantly decreased the levels of blood glucose and circulating lipopolysaccharide (LPS) and improved insulin resistance, inflammation, and lipid profile in diabetic rats induced by STZ and high-fat-high-sugar-diet. These anti-diabetic effects were attributed to the increased SCFAs content and the increased thickness of gut mucus layer, and were associated with the modulation of gut microbiota. Among the key phylotypes, Bacteroides and Bacteroidales S24-7 had the highest relative abundance in the rats receiving high-dose baicalein and showed positive correlation with the phenotypes related to the improvement of type 2 diabetes (T2DM). Our study supports the use of baicalein as a dietary supplement and a potential prebiotic for its ability to modify gut microbiota and to improve T2DM-related biochemical abnormalities.